Supporting fluid teams: a research agenda - Driskell, Tripp; Funke, Gregory; Tolston, Michael T.; Capiola, August; Driskell, James (Frontiers in Psychology, 2024)
This Perspective article presents a concise overview of critical research gaps and opportunities to support selection, training, and workplace design for fluid teams.